Comparison of complications associated with induction by misoprostol versus dilation and evacuation for second‐trimester abortion. Issue 3 (23rd June 2017) - Sonalkar, Sarita; Ogden, Shannon N.; Tran, Linda K.; Chen, Angela Y.
Abstract: Objective: To compare the frequency of complications between medical induction with misoprostol and dilation and evacuation (D&E) for second‐trimester uterine evacuation. Methods: In a retrospective cohort study, records were reviewed from all women who underwent second‐trimester uterine evacuation between 14 and 24 weeks of pregnancy at an academic hospital in the USA from January 2007 to December 2008. Total complications and serious complications were compared between medical induction and D&E, and clinical covariates associated with complications were assessed. Results: Overall, 465 women were included. At least one complication occurred in 28 (23.0%) of 122 women in the medical induction group, and 24 (7.0%) of 343 women in the D&E group ( P <0.001). One or more serious complications occurred in 4 (3.3%) women undergoing medical induction and 5 (1.5%) undergoing D&E ( P =0.251). Logistic regression analysis demonstrated that increasing pregnancy length ( P =0.003) and medical induction (as compared with D&E; P =0.004) were associated with complications. Conclusion: Although D&E resulted in fewer overall complications as compared with medical induction, the rate of serious complications did not differ between the two procedures. Abstract : Compared with induction using misoprostol, uterine evacuation by dilation and evacuation resulted in fewer overall complications, but not serious complications.